Teaching Material Development of Islamic Education Textbook for Students in SMK Muhammadiyah Delanggu - Uswatun Khasanah; Edy Muslimin (Institut Agama Islam Negeri (IAIN) Samarinda, 2021)
This study aims to develop teaching materials in the form of a textbook on Islamic education (PAI) subjects, which is valid based on the content, language, presentation, graphics, and practical feasibility aspects for students to use in learning. This type of research is research and development with the ADDIE development model, including analysis, design, development, implementation, and evaluation. However, this research has just implementeduntil the development stage. The data analysis technique employed in this research was descriptive statistics by calculating the percentage of validation scores. The data obtained came from validators consisting of three expert lecturers and respondents comprising four teachers and 34 students from SMK Muhammadiyah Delanggu. The results of the study revealed that the development of teaching materials in the form of Islamic education textbook for class XI for SMK/SMA/MA equals was declared valid (strong), fulfilling content feasibility aspects, linguistic feasibility aspects, presentation feasibility aspects, and graphic feasibility aspects. The overall average score of textbook validation was 94%, with a very valid (strong) category. In addition, the test results of teacher and student responses to the Islamic education textbook, respectively, were 90% and 95%, with very good (positively) criteria. Thus, this textbook positively affect studentsto be practical for them to use in learning.